Cryptococcus neoformans species complex isolates living in a tree micro-ecosystem. (April 2020) - Cogliati, Massimo; Patrizia, Procacci; Vincenzo, Conte; Esposto, Maria Carmela; Prigitano, Anna; Romanò, Luisa; Puccianti, Erika
Abstract: An old oak tree ( Quercus robur ), colonized by two different lineages of the Cryptococcus neoformans species complex (VNI and VNIV), was investigated to determine the distribution of cryptococcal yeasts in the different micro-habitats of the tree. The yeasts were isolated from most of the tree micro-habitats such as bark, trunk cavities, soil beneath the tree, arthropods living on the tree, and air. Sunlight exposure and low temperatures decreased in vitro growth of VNI isolates but not that of VNIV ones. Both VNI and VNIV strains isolated from the tree were able to produce basidiospores by mating assays. The investigated tree represents an environmental reservoir of C. neoformans, where it is able to survive and probably to reproduce, and from where blastospores and basidiospores, exposed to wind, water and contact with arthropods, birds, and mammals, may be dispersed in the environment as potential infectious propagules.